Psychometric properties of the Italian version of scale for outcomes in Parkinson’s disease psychiatric complications in Parkinson disease - Sofia Cuoco; Arianna Cappiello; Immacolata Carotenuto; Maria Autuori; Rossella Bisogno; Cristiano Sorrentino; Marco Aiello; Paolo Barone; Marina Picillo (Scientific Reports)
Abstract The Scales for Outcomes in Parkinson’s disease-Psychiatric Complications (SCOPA-PC) is a validated tool to score psychotic and compulsive symptoms in Parkinson’s disease (PD). We translated into Italian the SCOPA-PC and evaluated its psychometric properties and clinical correlates in different subgroups of PD patients. The scale underwent translation, back-translation, and cognitive pretesting before being administered to a calculated sample of 135 PD patients. All patients underwent a clinical interview, motor evaluation, cognitive screening test, behavioral and functional scales. We explored SCOPA-PC feasibility, acceptability, internal consistency, convergent validity, known-groups validity, and test–retest reliability. The mean SCOPA-PC score was 1.99 ± 2.09. The internal consistency was acceptable (α = 0.631); corrected item-total correlation was > 0.45 for most items. The significant and moderate correlation of the SCOPA-PC with other tools evaluating psychiatric symptoms indicated adequate convergent validity of the scale. The factor analysis disclosed two factors, with total variance equal to 50.19%. The reliability of SCOPA-PC was high especially in cognitively preserved patients not on medications for dementia, depression, psychosis and anxiety. The SCOPA-PC is a rapid and reliable screening tool for assessing psychotic and compulsive symptoms in PD. Our data support a role for the SCOPA-PC as a screening scale in early, non-demented PD.